2008
DOI: 10.1111/j.1365-2648.2008.04853.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ experiences of parenting a child with attention deficit hyperactivity disorder

Abstract: Mothering a child with attention deficit hyperactivity disorder is stressful and demanding, and mothers felt marginalized. Media portrayal of this disorder contributes to confusion related to causes, diagnosis and treatment choices. More education for healthcare professionals is needed to enable them to give appropriate guidance and support to enhance outcomes for children and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 32 publications
5
80
0
4
Order By: Relevance
“…The theme of worrying about the rest of the family is consistent with findings from previous studies in which caregivers shared concerns about the impact that the child's mental health needs had on the family (Lam & Mackenzie, 2002;Lefley, 1997;Lovenfosse & Viney, 1999). Also, the theme of being burdened and exhausted resonated with findings from other research studies (Goldberg-Arnold et al, 1999;Peters & Jackson, 2009;Scharer, 2002) in which caregivers reported being socially isolated due to caregiving demands, giving up employment in order to cope with their children's needs, and having multiple mental health appointments and calls from schools because of behavioral problems (Nelson, 2002;Peters & Jackson, 2009;Smith & Smith, 2000;Yantzi et al, 2006). Our study findings about the benefits of support groups with others going through similar experiences reinforce the work of other researchers who reported that access and participation in support groups helped to increase caregivers' ability to understand themselves and others, to talk and be listened to without judgment, to put their problems into perspective, and to make use of the group to provide an outlet for stress relief.…”
Section: Discussionmentioning
confidence: 61%
“…The theme of worrying about the rest of the family is consistent with findings from previous studies in which caregivers shared concerns about the impact that the child's mental health needs had on the family (Lam & Mackenzie, 2002;Lefley, 1997;Lovenfosse & Viney, 1999). Also, the theme of being burdened and exhausted resonated with findings from other research studies (Goldberg-Arnold et al, 1999;Peters & Jackson, 2009;Scharer, 2002) in which caregivers reported being socially isolated due to caregiving demands, giving up employment in order to cope with their children's needs, and having multiple mental health appointments and calls from schools because of behavioral problems (Nelson, 2002;Peters & Jackson, 2009;Smith & Smith, 2000;Yantzi et al, 2006). Our study findings about the benefits of support groups with others going through similar experiences reinforce the work of other researchers who reported that access and participation in support groups helped to increase caregivers' ability to understand themselves and others, to talk and be listened to without judgment, to put their problems into perspective, and to make use of the group to provide an outlet for stress relief.…”
Section: Discussionmentioning
confidence: 61%
“…Mothers have described their caregiver role to a child with ADHD as demanding and stressful (Peters & Jackson, 2009). Mother-teen conflicts and a greater degree of stress and conflicts within the family have also been reported with adolescents diagnosed with ADHD (Edwards, Barkley, Laneri, Fletcher, & Metevia, 2001).…”
Section: Families With Children Having Adhdmentioning
confidence: 99%
“…Some of the prominent needs reported by the parents are related to personal care needs (Plant & Sanders, 2007), management of adaptive behaviors (McCarthy, Cuskelly, Van Kraayenoord & Cohen, 2006), medical (Neely-Barnes & Marcenko, 2004), technical, financial and social needs (Verma & Kishore, 2009). While these needs are common in the context of other disabilities and nondisabilities, the intensity of the above is usually very high and unique in intellectual disabilities (Peshawaria, 1995;Verma & Kishore, 2009;James & Ashwill, 2007& Peters & Jackson, 2009.…”
Section: Introductionmentioning
confidence: 99%